2007
DOI: 10.1590/s0074-02762007005000055
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal humoral immune response to influenza vaccination in pediatric type-1 human immunodeficiency virus infected patients receiving highly active antiretroviral therapy

Abstract: Given that highly active antiretroviral therapy (HAART)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…79 The role of HIV-1 viral load for the influenza vaccination outcome is unclear as an association between viral load and immune response was reported in one study but not in another. 60,82 On the other hand, age and CD4+ T-cell counts do not seem to play a role. 79,83 During 2009, an upcoming pandemic infection of humans with swine influenza virus A(H1N1) was announced by WHO and a massive vaccination campaign was undertaken with both killed virus vaccines and live attenuated nasal sprays.…”
Section: Adaptive Immune Response To Different Vaccine Typesmentioning
confidence: 98%
See 1 more Smart Citation
“…79 The role of HIV-1 viral load for the influenza vaccination outcome is unclear as an association between viral load and immune response was reported in one study but not in another. 60,82 On the other hand, age and CD4+ T-cell counts do not seem to play a role. 79,83 During 2009, an upcoming pandemic infection of humans with swine influenza virus A(H1N1) was announced by WHO and a massive vaccination campaign was undertaken with both killed virus vaccines and live attenuated nasal sprays.…”
Section: Adaptive Immune Response To Different Vaccine Typesmentioning
confidence: 98%
“…80 In general, protective responses to different inactivated seasonal influenza vaccines in HIV-1 infected children, even if treated with HAART, are lower compared with healthy controls. 79,[81][82][83] The percentage of initial responders ranges 50-100% and in some cases, antibodies are almost completely lost after 6 mo from vaccination. 83 However, the establishment of CD8 + interferon-γ-secreting T-cells together with CD4 + interleukin (IL)-2-secreting T-cells upon vaccination may be more important than antibody formation as increase for influenza specific IgG3 but not IgG1 was reported.…”
Section: Adaptive Immune Response To Different Vaccine Typesmentioning
confidence: 99%
“…22,23 Compared with healthy individuals, HIV-infected individuals often have reduced immune responses to various immunisations (e.g. influenza vaccination, 24,25 hepatitis B virus vaccination 26 and pneumococcal vaccination 27 ). Nevertheless, vaccination remains a common clinical tool to reduce the risk of secondary infections in people with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…In HIV-uninfected subjects 9-17 years of age who were immunized with 15 µg or 30 µg of the same unadjuvanted vaccine given to Group B in the current study, 96% and 100%, respectively, achieved HAI antibody titers 40 [18]. Multiple other studies have reported lower immunogenicity of influenza vaccines and lower proportions of HIV-infected vaccinees achieving protective HAI antibody titers than in persons without HIV infection [5,8,11,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 43%
“…In addition, an association between poor response to influenza vaccines and higher viral load and/or lower current or nadir CD4 counts has been reported [21,[29][30][31]. Studies of AS03-and MF59-adjuvanted vaccines in healthy adults and children report higher rates of seroprotection and seroconversion or achievement of comparable immunogenicity with much smaller doses of antigen with adjuvanted vaccine [18,20,32,33].…”
Section: Discussionmentioning
confidence: 99%